Mental State Verb Production as a Measure of Perspective Taking in Narrations of Individuals With Down Syndrome - Neitzel, Isabel; Penke, Martina (Frontiers in Communication, 2021)
Introduction: Perspective taking is an important ability to enrich narrations by empathizing with a real or fictional character. Mental state verbs (MSV) are a good indicator for this ability as they serve to reflect the mindset that the narrator attributes to a protagonist. Especially syntactic abilities have been argued to be relevant for MSV use. Investigating persons with Down Syndrome (DS) is likely to provide important insights into the relationship of MSV use and syntactic abilities: MSV are mostly used in complex sentence structures, which are a frequent difficulty for individuals with this syndrome. Indeed, previous investigations have found first evidence for impaired MSV production in individuals with DS, indicating a link to syntactic abilities and expressive vocabulary. Our aim was to provide evidence on MSV production and on the syntactic context of MSV production in individuals with DS and to target a possible connection to both cognitive and language abilities using specific language assessments. Typically-developing (pre-)school children were included as a comparison group to identify impaired respectively developmentally-adequate performance. Method: 28 individuals with Down syndrome (aged 10;0 to 20;1 years) participated in a battery of cognitive, narrative and language measures. MSV-performance and syntactical context of MSV use were compared to data from 33 typically-developing children aged 3 to 9 years. We also analyzed the relationship between MSV production and language performance (vocabulary, syntax measures, mean length of utterance). Results: The total number and types of MSV used were comparable for individuals with DS and TD. Moreover, a syntactic analysis indicated that individuals with DS and TD use MSV in the same syntactic contexts. Nevertheless, the syntactic difficulties of participants with DS are reflected in their frequent use of MSV in sentence-fragments. Correlations over the DS group yielded that syntactic abilities were not decisive for the richness and diversity of MSV in narrations. Conclusion: Our findings suggest a comparable performance in MSV use in individuals with DS and school-aged TD children. The data indicate that MSV production is possible even with an impaired syntax suggesting unimpaired perspective taking abilities in individuals with DS.